2017
DOI: 10.1002/adsc.201700314
|View full text |Cite
|
Sign up to set email alerts
|

Omniligase‐1: A Powerful Tool for Peptide Head‐to‐Tail Cyclization

Abstract: Strategies for the efficients ynthesis of peptide macrocyclesh ave been al ong-standing goal. In this paper, we demonstrate the use of the peptide ligase termedo mniligase-1 as av ersatile and broadly applicable enzymatic toolf or peptide cyclization. Severalh ead-to-tail (multi)cyclic peptides have been synthesized, including the cyclotide MCoTI-II. Cyclization ando xidative foldingo ft he cyclotide MCoTI-II were efficiently performed in ao ne-pot reactiono na1 -gram scale.T he native cyclotide was isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 35 publications
1
110
0
Order By: Relevance
“…Over the years, a variety of different technologies for constraining peptide structures have been described, including side‐chain‐to‐side‐chain crosslinks and the use of small‐molecule organic scaffolds . We recently established an efficient chemoenzymatic peptide synthesis (CEPS) strategy by using omniligase‐1‐catalyzed head‐to‐tail cyclization for the preparation of various (multi)cyclic peptides, such as the cyclotide MCoTI‐II . Although the cystine‐knotted core of cyclotides represents a promising scaffold for drug design, the majority of disulfide‐rich peptides form isomeric mixtures upon oxidation, which further emphasizes the need for a straightforward, sequence‐independent methodology that enables the manufacture of isomerically pure multicyclic constructs.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, a variety of different technologies for constraining peptide structures have been described, including side‐chain‐to‐side‐chain crosslinks and the use of small‐molecule organic scaffolds . We recently established an efficient chemoenzymatic peptide synthesis (CEPS) strategy by using omniligase‐1‐catalyzed head‐to‐tail cyclization for the preparation of various (multi)cyclic peptides, such as the cyclotide MCoTI‐II . Although the cystine‐knotted core of cyclotides represents a promising scaffold for drug design, the majority of disulfide‐rich peptides form isomeric mixtures upon oxidation, which further emphasizes the need for a straightforward, sequence‐independent methodology that enables the manufacture of isomerically pure multicyclic constructs.…”
Section: Figurementioning
confidence: 99%
“…We evaluated the general applicability of triple‐C locking by synthesizing a library of peptides that differed in the length and sequence, which contained both two cysteine and two Aha residues combined with a C‐terminal elongated carboxamidomethyl ester (Cam ester) . Considering the requirement for efficient omniligase‐1‐catalyzed cyclization to be ≥13 amino acids, we first attempted cyclization of the linear 16‐mer peptide 2 3333 (H‐SYCQGA[Aha]KSE[Aha]KFGCK‐ OCam ‐ L ‐OH). Enzymatic cyclization (CEPS) gave the monocyclic peptide c 2 3333 within 30 min (Figure A).…”
Section: Figurementioning
confidence: 99%
“…The use of enzymes as biocatalysts in peptide cyclization increasingly attracted attention due to their nontoxic nature, cost‐effectiveness, and high chemoselectivity. With the development of protein engineering biotechnology, a variety of enzymes have been exploited for peptide cyclization, such as butelase, trypsin, protease OaAEP1b, prenyl transferase, PatG, sortase, subtiligase, peptiligase, thioesterase, glutathione S‐transferase, transglutaminase, etc. In 2002, Kohli et al discovered an isolated thioesterase, which displayed the capability of catalyzing the cyclization of linear peptides tethered to a carrier protein via a phosphopantetheine linker.…”
Section: Strategies To Develop Cyclic Peptides Into Therapeutic Agentsmentioning
confidence: 99%
“…

We report aone-pot ligation/cyclization technology for the rapid and clean conversion of linear peptides into tricyclic peptides that is based on using tetravalent scaffolds containing two benzyl bromide and two alkyne moieties.These react via CLIPS/CuAACreactions with cysteines and azides in the peptide.Flexibility in the scaffolds is key to the formation of isomerically pure products as the flexible scaffolds T4 1 and T4 2 mostly promote the formation of single isomeric tricycles while the rigid scaffolds T4 3 and T4 4 do not yield clean products. [12][13][14][15][16][17][18][19][20][21][22][23] In 2005, our group introduced "CLIPS technology" (chemical linkage of peptides onto scaffolds), which involves the tandem ligation/cyclization of tris(cysteine)-containing linear peptides with a,a',a''-tribromomesitylene (T3)t og ive the corresponding bicyclic peptides. We also observed that azides at the peptide termini and cysteine residues in the center gave better results than compounds with the functional groups placed the other wayr ound.

Cyclic peptides have emerged as ap romising class of drug compounds [1][2][3][4] showing aw ide therapeutic window that ranges from antifertility [5] to anticancer [6][7][8] and antiviral [9][10][11] applications.A st he number of cyclic peptides entering clinical trials has drastically increased over the last years, [6] the search for novel synthetic routes to multicyclic peptides has received significant interest.

…”
mentioning
confidence: 99%
“…[25] Currently,c omplex syntheses impede the large-scale production of vancomycin-like drugs,and complicate structural diversification processes aimed at optimizing their biological activities. [26] Examples of synthetic tricyclic peptides have been reported as the groups of both Ruchala [17] and Wu [18] used either a T h -o raD 2h -symmetric scaffold to assemble linear peptides into tricycles,w hile Suga, [19] Nuijens, [20] and our group [21] used various types of backbone cyclization in combination with T3 CLIPS.T hese and other examples emphasize the interest in multicyclic peptides although the formation of multiple isomers,laborious reaction procedures, as well as difficulties in generating structural diversity remain delicate issues.CLIPS reactions of tetrakis(cysteine)-containing peptides with 1,2,4,5-tetrabromodurene (T4)w ould provide as traightforward route to manufacturing tricycles. However,t his reaction yields am ixture of six different regioisomers, [18] which renders this strategy not suitable for atherapeutic development trajectory (Figure 2a).…”
mentioning
confidence: 99%